'Up to now I am suffering': justice, sexual violence and disability amongst refugees in Uganda. (2015) - Smith-Khan, Laura; Crock, Mary; McCallum, Ron; Saul, Ben
Sexual violence is a common feature of persecution, and of the displacement situations that follow it. Such violence can cause serious physical, psychological and social harm, sometimes amounting to disability. Despite formal obligations on host states and international bodies to ensure the rights of refugees with disabilities, many challenges exist to promoting access to justice for refugee survivors of sexual violence. Through the lens of international law, this article considers two conceptualisations of justice and how well it is achieved for refugee survivors of sexual violence living in Uganda. Drawing on recent fieldwork, it will argue that despite some positive developments, there remain significant barriers to true justice for this group.